Perancangan Sistem Informasi Human Resources Development Pada PT. Semacom Integrated - Chairul Anwar; Joko Riyanto (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2019)
PT. Semacom Integrated merupakan perusahaan yang bergerak dalam bidang panel listrik. Perusahaan ini perlu mengelola data pegawai tetapi belum mempunyai sistem informasi khusus untuk mengelola data pegawai tersebut agar memudahkan dalam pengelolaan data, pengontrolan serta meningkatkan pekerjaan Human Resource Development, Pimpinan dan Pegawai. Teknologi pemrograman dan database sebagai media penyimpanan diyakini sampai saat ini masih sangat berguna dalam membantu menklasifikasikan data informasi. Pengembangan sistem yang digunakan dalam penelitian ini adalah waterfall. Metode ini terdiri dari requirement gathering, analysis, system design, implementation, testing, dan maintenance. Adapun tools yang digunakan dalam penelitian ini adalah System Operating 10 Pro 64 Bit, Notepad++. Sedangkan, database yang digunakan sebagai penyimpanan data adalah Xampp. Hasil dari penelitian ini berupa sistem informasi kepegawaian. Sistem ini meliputi daftar pegawai daftar SK kerja, daftar prestasi, daftar hukuman, surat kontrak, surat keterangan, surat perintah dan surat peringatan, dan lain-lain. Sistem ini dirancang untuk memudahkan Human Resource Development dalam pencarian dan pengelolaan data kepegawaian pada PT. Semacom Integrated. Design of Human Resources Development Information Systems for PT. Semacom Integrated Abstract: PT. Semacom Integrated is a company engaged in the field of electrical panels. This company needs to manage employee data but does not yet have a special information system to manage employee data to facilitate data management, control and improve the work of Human Resource Development, Leaders and Employees. It is believed that programming and database technology as storage media is still very useful in helping to classify information data. The development of the system used in this study is a waterfall. This method consists of requirements gathering, analysis, system design, implementation, testing, and maintenance. The tools used in this research are System Operating 10 Pro 64 Bit, Notepad ++. Meanwhile, the database used as data storage is Xampp. The results of this study are in the form of staffing information systems. This system includes a list of employees, a list of work decree, a list of achievements, a list of penalties, a contract, a certificate, a warrant and a warning letter, and others. This system is designed to facilitate Human Resource Development in the search and management of staffing data at PT. Semacom Integrated Keywords: Personnel Information System, Waterfall Model, Human Resource Development